(untitled) (Bangladesh Journal of Animal Science, 2013)
The experiment was conducted to study the comparison on biomass production of fodder germplasm. Para (Brachiaria mutica Stapf.), German (Echinochloa crusgalli L.) and Dhal (Hymenachne pseudointerrupta C. Muell) grasses were cultivated in a completely randomized design (CRD). The whole area was divided into nine plots. The area of each unit plot was 6 m x 6 m. Number of cuttings were 16,000 /hectare where Plant to Plant distance was 16 cm and row and raw distance was 16 cm. Equal amount of organic and chemical fertilizer were applied in all cutting. The fodders were first harvested after 60 days of planting, second and third after successive 60 days of re-growth. The findings of the study showed that fresh biomass (p<0.01) and dry biomass yield (p<0.05) of three fodder germplasm differed significantly. Crude protein and organic matter yield were significant (p<0.01) only in the second cutting. German grass was showed significantly higher in CP and OM yield (p<0.01) at second cutting than other grasses. However, no significant effect on plant height was observed among three grasses. From the above findings it may be concluded that among the three fodder germplasm, German fodder showed best result in respect of biomass production. DOI: http://dx.doi.org/10.3329/bjas.v42i1.15772 Bang. J. Anim. Sci. 2013. 42 (1): 35-39